1998
DOI: 10.1080/02772249809358639
|View full text |Cite
|
Sign up to set email alerts
|

Organotin pollution in Malta coastal zone

Abstract: The speciation of organotins in seawater, surface microlayer and sediments in the marine environment of Malta is described. Concentrations of tributyltin (TBT) in bulk seawater inside the harbours were as high as 0.3 μg Sn L -1 but were below detection limits (5 ng Sn L -1 ) in open sea, 1.6 km offshore. In sediments, TBT levels were highest for the yacht marinas and ranged between 0.03 and 1.5 ug Sn g -1 . Dibutyltin is more common in the surface microlayer than TBT. Diphenyl and monophenyltin were found infr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The territory comprising the island of Malta was divided into grids of approximate size 7.8 km 2 and at least one sample was taken from each grid area (Fig. 1) …”
Section: Sampling Of Dustmentioning
confidence: 99%
See 1 more Smart Citation
“…The territory comprising the island of Malta was divided into grids of approximate size 7.8 km 2 and at least one sample was taken from each grid area (Fig. 1) …”
Section: Sampling Of Dustmentioning
confidence: 99%
“…1,2 In Malta, ship repair and maintenance activities take place at the drydocks which are located within the Grand Harbour area, in close proximity to densely populated urban zones. A preliminary unpublished study 3 carried out in our laboratory in 2000 had indicated the presence, in significant amounts, of MBT, DBT and TBT in settled urban dust collected from rooftops in two villages in the southeastern part of Malta, which is the site of the drydocks.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] It appears likely that these compounds might be more ubiquitous than is presently apparent, and they could have remained In vitro methylation of tributyltin 905 unidentified due to the fact that attention may have been reserved solely for specifically targeted organotin forms. It is not uncommon to see reports in the literature where FPD-generated gas chromatograms are presented that contain more peaks than are identified and discussed by the authors, and methylbutyltins could well be among such unidentified peaks.…”
Section: Discussionmentioning
confidence: 94%
“…This is the site of one of the major yacht marinas on this central Mediterranean island; the creek also receives considerable runoff from one of the valley systems in Malta. This site was chosen as it provides an organic-matter-rich calcitic sediment that is known to be moderately contaminated with organotins; TBT and methylbutyltins had been identified in various sediments from this marina 2 and, therefore, biota resistant to TBT and possibly capable of transforming organotins biochemically to methylated forms were considered to be present in the sediment. Around 10 l 3 of seawater was collected from a depth of 1 m, and around 2 kg of a greyishblack sediment were removed from the sea bed at 2.5 m water depth using a grab sampler.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation